Paysages transalpins : la vallée du Pô et les enjeux de l’écriture paysagère dans les Géographies Universelles (1810-1934) - Federico Ferretti (Projets de Paysage)
The first three Universal Geographies by Malte Brun (1810-1829), Elisée Reclus (1876-1894) and Paul Vidal de la Blache’s fellows (1927-1947) are the great and well-known representations of the contemporary world produced by French geography between the 19th and the first half of the 20th centuries. How do they concern the writing of landscape as it has been developed in their age ? We analysed their texts about this problem, starting by an example little but significant because of the density of its human landscapes and their historical relevance : the Po valley.